Is Pertussis Infection Neglected in China? Evidence from a Seroepidemiology Survey in Zhejiang, an Eastern Province of China - He, Hanqing; Yao, Pingping; Zhou, Yang; Deng, Xuan; Pan, Jinren (PloS one, 2016)
The resurgence of pertussis has occurred in many countries. However, the epidemiological profiles of pertussis cannot be well understood by the current surveillance system in China. This study was designed to investigate the age specific serologic evidence of antibodies against pertussis, and to offer information regarding the existence of pertussis infection in Zhejiang Province, China. A cross-sectional serosurvey was carried out in 6 counties of Zhejiang Province during September and October of 2014. The immunoglobulin G-pertussis toxin (IgG-PT) levels were measured quantitatively with a commercially available enzyme-linked immunosorbent assay (ELISA). The antibody activities were expressed in the Food and Drug Administration (FDA)-U/ml and a level ≥30 FDA-U/ml was considered seropositive. An IgG-PT >80 FDA-U/ml indicated recent pertussis infection if the patient had not received immunization with the pertussis vaccine within the last year. The mean IgG-PT seropositivity rate among the 2107 subjects was 33.32% with a geometric mean concentration of 17.73 (95% confidence interval: 16.90-18.60) FDA-U/ml. The difference in the seropositivity rates reached significant means among the different age groups (waldχ2 = 198.41, P<0.0005), and children aged 3 years had the highest percentage (63.24%) of undetectable IgG-PT level. Of the 1707 subjects ≥3 years of age, 169 (9.90%) had evidence of a recent infection. The highest proportion of IgG-PT levels ≥80 FDA-U/ml was found in ≥60 years age group followed by 11-15 and 16-25 years age groups. This study indicates the rather lower IgG-PT level sustained 1 year after the acellular pertussis vaccine booster dose, and substantial proportion of population susceptibility to pertussis in Zhejiang Province, China. Moreover, pertussis infection is not uncommon; it was estimated that 10% of subjects were recently infected approximately within the last 100 days. We highly suggest that the surveillance capacity should be strengthened and consider introducing booster dose that protect against pertussis in 6 years old children.